A new B-spline type approximation method for non-smooth functions. (July 2023) - Amat, Sergio; Levin, David; Ruiz-Álvarez, Juan; Yáñez, Dionisio F.
Abstract: In this letter we present a non-linear modification of classical quadratic and cubic splines following the inspiration of the PPH (piecewise polynomial harmonic) interpolation method. The objective is to get rid of the oscillations that appear close to jump discontinuities in the function when we approximate using a classical spline.